2010
DOI: 10.1111/j.1440-172x.2010.01879.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medical emergency teams on patient outcome: A review of the literature

Abstract: This paper presents a review of literature on the impact of the medical emergency team (MET) on inpatient mortality, cardiopulmonary arrests or unscheduled intensive care unit (ICU) admissions. A total of 14,172 abstracts and 98 full text papers were reviewed. In total, 24 met the inclusion criteria, 2 used a cluster-randomized controlled trial, 11 before and after, 6 retrospective analyses, 4 prospective cohorts and 1 not reported. There is moderate to strong evidence that METs are associated with decreased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…All aggregate data outcomes are placed on the hospital's quality dashboard, accessed by employees or physicians as part of the UCH value of transparency to improve patient care. The MET and code data report the desired goal, which is to decrease code blue occurrences with an associated increase in MET calls on medicalYsurgical units, consistent with reports in the literature by Laurens and Dwyer (2010) and DeVita et al (2004). Outcomes and numbers of code versus MET calls over time can be seen in Figure 2.…”
Section: Program Outcomes Datasupporting
confidence: 56%
See 1 more Smart Citation
“…All aggregate data outcomes are placed on the hospital's quality dashboard, accessed by employees or physicians as part of the UCH value of transparency to improve patient care. The MET and code data report the desired goal, which is to decrease code blue occurrences with an associated increase in MET calls on medicalYsurgical units, consistent with reports in the literature by Laurens and Dwyer (2010) and DeVita et al (2004). Outcomes and numbers of code versus MET calls over time can be seen in Figure 2.…”
Section: Program Outcomes Datasupporting
confidence: 56%
“…Murray and Kleinpell (2006) developed nurse-led protocols that met the standards of physicianapproved orders. While questions have been raised as to the effectiveness of METs, a comprehensive review of the literature by Laurens and Dwyer (2010) that included 14,172 abstracts and 98 full texts reported that there is moderate to strong evidence that METs are associated with decreased mortality and cardiac arrest, but evidence is weak for reducing ICU admission rates. At UCH, the Code Team is multidisciplinary, with ICU registered nurses (RNs), physicians, and respiratory therapists taking call using a code pager.…”
Section: Background and Literature Reviewmentioning
confidence: 98%
“…Multiple reviews and meta-analyses have been done reaching conflicting conclusions on the impact of RR/METs on hospital mortality. [6, 810] It is possible, therefore, that there is truly no such impact of this intervention. Notably, however, multiple studies have reported on the negative association of delays in ICU admission (prolonged TtT ICU ) and mortality—in the emergency department,[37] throughout the hospital,[38] post-operatively,[39] and from hospital wards [40].…”
Section: Discussionmentioning
confidence: 99%
“…The development of medical emergency/rapid response teams to immediately evaluate, treat, and triage patients outside of the ICU with potentially critical illnesses has grown. 27 While data on their impact are mixed, [28][29][30][31] staff satisfaction has been seen to improve with their implementation. 32,33 While no standard exists, many of these teams include an intensivist.…”
Section: Intensivist Presence and The Hospitalmentioning
confidence: 99%